Gestão de custos em uma instituição federal de ensino: proposta de modelo de apuração com base no custeio ABC - Costa, Aline Pereira (2019)
The cost informations are very important for the public manager to possibility analyze adequate the quality and effectiveness of the public service. This study shows that efficient cost management allows to achieve the improvement in the allocation of resources in the IFES (Federal Institutions of Higher Education). Thus, it proposes a costing model for the Federal Institute of Southeast Minas Gerais Barbacena campus, based on ABC costing, demonstrating the applicability of the model by means of a survey of the costs of the institution's undergraduate courses. This search its classified in: descript, explorate, bibliographic and documental, and, about the problem, shows qualitative aspects. The results obtained allow us to consider that the fundamentals of the ABC methodology allow to measure the costs of the degrees, provide subsidies to decision making and can be extended to several services of the institution under analysis, besides being a model for similar institutions.